1997
DOI: 10.1161/01.cir.96.11.3904
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Mapping of the Common Atrial Flutter Circuit in the Right Atrium

Abstract: Interindividual variations occur in the right atrial circuit of common atrial flutter, with constant activation through the cavotricuspid isthmus. A variable zone of block forms the posterior limit. Fusion around the SVC can occur, and ascending medial septal activation does not follow a consistent pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
146
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(158 citation statements)
references
References 22 publications
10
146
1
1
Order By: Relevance
“…5,6 The broad band of peritricuspid activation narrows as it enters the cavotricuspid isthmus, slows in the medial portion, ascends the septum and crosses the roof in front of the SVC or, more rarely fusing around it. 15 In the present study, electroanatomic mapping demonstrated that the activation pattern of typical CCW AFL is consistent with that described previously. 16 …”
Section: Global Electroanatomic Mapping During Typical Ccw Aflsupporting
confidence: 92%
“…5,6 The broad band of peritricuspid activation narrows as it enters the cavotricuspid isthmus, slows in the medial portion, ascends the septum and crosses the roof in front of the SVC or, more rarely fusing around it. 15 In the present study, electroanatomic mapping demonstrated that the activation pattern of typical CCW AFL is consistent with that described previously. 16 …”
Section: Global Electroanatomic Mapping During Typical Ccw Aflsupporting
confidence: 92%
“…7,10,11 Radiofrequency current was applied for 60 seconds (maximum tip temperature set at 70°C, maximum output 50 W). Success was defined by (1) noninducibility of the clinical arrhythmia after the procedure, (2) establishment of a line of conduction block over the cavo-tricuspid isthmus (AFL patients), or (3) establishment of a line of conduction block between 2 anatomic boundaries (eg, scar areas in IART patients).…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…In the circuit, a critical component of slow conduction is frequently present, often located in the isthmus of right atrial tissue, which is between the tricuspid annulus, the inferior vena cava, and the coronary sinus with the eustachian valve and ridge. 5,6 Occasionally, the circuit curves around a scar or surgical incision in the atrium or is confined to the left atrium. Endocardial activation mapping and stimulation studies are required to determine the circuit.…”
Section: Mechanism and Types Of Macroreentrant Tachycardiasmentioning
confidence: 99%
“…Endocardial activation mapping and stimulation studies are required to determine the circuit. 5,6 Of the different types of AFl shown in Figure 1, the typical, common, or type 1 flutter is the most frequent. In this type of flutter, right atrial activation rotates in a counterclockwise direction.…”
Section: Mechanism and Types Of Macroreentrant Tachycardiasmentioning
confidence: 99%